PROFIL DOPPLER TRANSKRANIAL PADA GANGGUAN FUNGSI KOGNITIF PASCASTROKE ISKEMIK - Farida, Salim Harris, Mohammad Kurniawan (NEURONA, 2014)
INTRODUCTION ATHEROSCLEROSIS IS ONE OF THE MOST COMMON CAUSE OF ISCHEMIC STROKE ESPECIALLY IN THE INTRACRANIAL VESSELS ATHEROSCLEROTIC PLAQUE CAN ACTIVATE BLOOD CLOTTING MECHANISM AND INHIBIT BLOOD FLOW IN ARTERIES SO IT WILL ACUTELY DIMINISHED THE BRAIN FUNCTION IN THE LOCALIZED AREAS IMPAIRED COGNITIVE FUNCTION MAY OCCUR AFTER A STROKE WHICH AFFECT THE QUALITY OF LIFE OF STROKE PATIENTS